2022 International Conference on Advanced Learning Technologies (ICALT) 2022
DOI: 10.1109/icalt55010.2022.00068
|View full text |Cite
|
Sign up to set email alerts
|

Toward Code Review Notebooks

Abstract: Peer code review has proven to be a valuable tool in software engineering. However, integrating code reviews into educational contexts is particularly challenging due to the complexity of both the process and popular code review tools. We propose to address this challenge by designing a code review application (CRA) aimed at teaching the code review process directly within existing online learning platforms. Using the CRA, instructors can scaffold online lessons that introduce the code review process to studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In a previous study [8], we presented a code review application that could be used to scaffold code review notebooks. Our evaluation using standard instruments for measuring user experience (System Usability Scale [5] and the short version of the User Experience Questionnaire [20]) suggested that students rated the usability of the code review notebook and the underlying code review application positively.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [8], we presented a code review application that could be used to scaffold code review notebooks. Our evaluation using standard instruments for measuring user experience (System Usability Scale [5] and the short version of the User Experience Questionnaire [20]) suggested that students rated the usability of the code review notebook and the underlying code review application positively.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Textual explanations regarding the code review process and code linting were intercalated with images and code snippets. Code snippets were presented using the code review application [8], which allowed students to annotate each line of code with comments. Furthermore, a text input application was used to allow students to answer open-ended questions.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of their coursework, students completed an in-class online lesson consisting of an ungraded 45-minute exercise. The exercise comprised a code review notebook [5] covering JavaScript code style standards. Code review notebooks allow educators to scaffold pedagogical scenarios that introduce the code review process to learners through code snippets, following a template resembling computational notebooks.…”
Section: Scenariomentioning
confidence: 99%
“…These reviews consist of a developer submitting code for review and then another developer reviewing the submitted code by adding comments to specific lines of code. The code review application allows an instructor to simulate the code review process within an online learning exercise resembling a computational notebook [13]. Students are shown a code snippet and are asked to analyze it for potential issues.…”
Section: Learning Scenariomentioning
confidence: 99%